2003
DOI: 10.1056/nejmoa030254
|View full text |Cite
|
Sign up to set email alerts
|

Initial Treatment of Immune Thrombocytopenic Purpura with High-Dose Dexamethasone

Abstract: A four-day course of high-dose dexamethasone is effective initial therapy for adults with immune thrombocytopenic purpura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
220
4
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(239 citation statements)
references
References 20 publications
(28 reference statements)
12
220
4
3
Order By: Relevance
“…We have obtained a persistent response rate of 66.7% (32/48 evaluable adult patients) without any therapy, whereas in the Cheng et al study a persistent response rate of 42% was reported. 21 Furthermore, our data seem to be similar to those of Borst et al, 23 who more recently reported a long-term response of 59%. However, they observed an adverse event rate of 22%, and in our 2 studies adverse event rates were 13.5% and 2.1%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We have obtained a persistent response rate of 66.7% (32/48 evaluable adult patients) without any therapy, whereas in the Cheng et al study a persistent response rate of 42% was reported. 21 Furthermore, our data seem to be similar to those of Borst et al, 23 who more recently reported a long-term response of 59%. However, they observed an adverse event rate of 22%, and in our 2 studies adverse event rates were 13.5% and 2.1%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained by the GIMEMA multicenter pilot study in adults are comparable to those recently reported by Cheng et al 21 for the initial response rate (85% vs 85%). However, the relapse rate of 22% observed in the GIMEMA study is very different from that observed by Cheng et al, who reported a 50% relapse rate within 6 months from response achievement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A previous study also showed that Dex monotherapy was related to a higher incidence of posttherapeutic relapse (50%), although the initial remission was high (85%). 15 Late relapse is one of the critical problems in ITP treatment, [1][2][3][4] and there is an ongoing need to develop strategies to suppress relapse. Our findings indicated that additional courses of Dex (two to six total courses) and/or tapering PSL could significantly suppress relapse (21%) compared with PSL (37%).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood ITP is typically a disease of acute onset; more than 80% of children will have a spontaneous and permanent remission within 1 year of onset [2]. In contrast, adults tend to have more persistent ITP [3], although recent studies suggest that there is a tendency for certain patients to improve with time [3][4][5][6]. Rarely, life-threatening bleeding occurs, with intracranial hemorrhage being the principle cause of death [1,7].…”
Section: Introductionmentioning
confidence: 99%